Números complexos: uma abordagem matricial - Silva, Samuel Macedo da (2017)
The present dissertation aims to present a different way of working the complex numbers in Basic Education, that occurs through ordered pairs or algebraic form. We use basic knowledge of matrix algebra. Here we present the matrix form of the complex numbers and demonstrate their basic properties, comparing them with those present in the mathematical literature. It stands out the matrix representation of the famous equation of Euler. Finally, a proposal of activity, based on problem solving, is presented to be developed by teachers and students of Basic Education.